The Status of Posttraumatic Growth in Earthquake Survivors, Three Years After the Earthquake in East Azerbaijan - Mustafa Mardani; Fardin Alipour; Ramezanali Qaderi; Mohammad Sabzi Khoshnam (Health in Emergencies & Disasters Quarterly, 2017)
Background: Experience of difficult incidents, besides its negative and adverse consequences, can have positive consequences and lead to the growth of people in several areas. Evaluating the status of posttraumatic growth in earthquake survivors could help better understand the various dimensions of this incident. The present study aimed to evaluate the status of posttraumatic growth in East Azerbaijan earthquake survivors. Materials and Methods: This study is a cross-sectional and descriptive-analytical research. The study population consisted of East Azerbaijan earthquake survivors and the study sample included 295 survivors randomly selected from those who were eligible for the study. The research tools were a demographic questionnaire and posttraumatic growth inventory. Results: The mean (SD) age of the participants was 43(14.3) years, and 50.5% of them were male. The mean (SD) of the posttraumatic growth score of the study sample was 48.25(21.18). The findings of this study showed that among posttraumatic growth dimensions, “spiritual changes” (11.11[5.1]) and “connecting with others” (4.9[2.3]) had the highest score, while the “new possibilities” got the lowest score (16.3[7.19]). Conclusion: Posttraumatic growth issue requires further attention in the mental and social health policies. The study results indicate that despite the many problems that the earthquake creates for people, dealing with this disaster leads to positive psychological effects on people, too.